2012
DOI: 10.1002/ajmg.a.35214
|View full text |Cite
|
Sign up to set email alerts
|

Screening of congenital heart disease patients using multiplex ligation‐dependent probe amplification: Early diagnosis of syndromic patients

Abstract: Recurrent copy number variants (CNVs) are found in a significant proportion of patients with congenital heart disease (CHD) and some of these CNVs are associated with other developmental defects. In some syndromic patients, CHD may be the first presenting symptom, thus screening of patients with CHD for CNVs in specific genomic regions may lead to early diagnosis and awareness of extracardiac symptoms. We designed a multiplex ligation-dependent probe amplification (MLPA) assay specifically for screening of CHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 20 publications
4
45
1
1
Order By: Relevance
“…8 Additional MLPA probes were used and family MC061 was found to have a 2q37.3 duplication. 8 Twenty-one families of this series were tested for a panel of 13 sarcomeric genes in a second collaborative study, 7 and disease-causing variants were found only in the alpha cardiac heavy chain myosin gene (MYH6), in three families (MC027 p.(Cys539Arg), MC053 p.(Lys543Arg) and MC081 p.(Arg17His)). These 21 families were selected out of the Registry because at least one affected individual had ASD (for details, see Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Additional MLPA probes were used and family MC061 was found to have a 2q37.3 duplication. 8 Twenty-one families of this series were tested for a panel of 13 sarcomeric genes in a second collaborative study, 7 and disease-causing variants were found only in the alpha cardiac heavy chain myosin gene (MYH6), in three families (MC027 p.(Cys539Arg), MC053 p.(Lys543Arg) and MC081 p.(Arg17His)). These 21 families were selected out of the Registry because at least one affected individual had ASD (for details, see Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Some families of this cohort were screened for other genes or another MLPA test and are reported elsewhere. 7,8 For details on the enrolled families, see Supplementary Table S1. All variants were submitted to LOVD (www.lovd.nl/3.0/home).…”
Section: Genetic Analysismentioning
confidence: 99%
“…Recently, Sørensen et al (12) examined 402 CHD patients (378 with isolated CHD and 24 with extra cardiac malformations) with a specific multiplex ligation-dependent probe amplification designed for CHD screening. They identified 14 rare CNVs in 13 (3.2%) patients, with >80% of the detected imbalances found in children younger than 5 y.…”
Section: Discussionmentioning
confidence: 99%
“…Although a single biomarker can be used to diagnose a disease, but there are issues where a single biomarker alone cannot accurately predict occurrence of the disease [6]. To address this multi analyte detection various molecular methods have been developed such as; multiplex polymerase chain reaction analysis [7], multiplex ligation-dependent probe amplification [8], DNA microarray for gene expression or SNP detection assays [9], protein microarray [10], phage display [11] etc. These methods, however, are extremely powerful for multianalyte detection but they suffer due to their cost and inability of miniaturization for the onsite analysis.…”
mentioning
confidence: 99%